Queuing Delay Analysis for Wavelength Routing Optical Satellite Networks Over Dual-Layer Constellation - Jingkai Yang; Qiwen Ran; Jing Ma (IEEE Photonics Journal)
Optical satellite networks (OSN) utilizing wavelength division multiplexing (WDM) inter-satellite links (ISLs) and wavelength routing is becoming a new trend in constructing high-speed, large-capacity, and low-latency global network systems. Since the number of wavelength channels for the WDM ISLs is limited, the traffic requests might incur queuing delays due to the wavelength channel congestion. To evaluate the delay-tolerance characterization of dual-layer wavelength routing OSN (DWROSN), the ISLs arrival coefficient (IAC) is proposed to construct the queuing model. Simulation results are compared with theoretical results in terms of queuing length and queuing delays. The results show that the traffic intensity, number of wavelength channels, and node degree of the satellite have an impact on the queuing characterization of the DWROSN. The queuing model with the IAC can efficiently evaluate the queuing characterization of the DWROSN.